National Museums and Nation-building in Europe 1750-2010 Mobilization and legitimacy, continuity and change - Aronsson, Peter; Elgenius, Gabriella (Taylor & Francis, 2014)
Europe's national museums have since their creation been at the centre of on-going nation making processes. National museums negotiate conflicts and contradictions and entrain the community sufficiently to obtain the support of scientists and art connoisseurs, citizens and taxpayers, policy makers, domestic and foreign visitors alike. National Museums and Nation-building in Europe 1750-2010 assess the national museum as a manifestation of cultural and political desires, rather than that a straightforward representation of the historical facts of a nation. National Museums and Nation-building in Europe 1750-2010 examines the degree to which national museums have created models and representations of nations, their past, present and future, and proceeds to assess the consequences of such attempts. Revealing how different types of nations and states - former empires, monarchies, republics, pre-modern, modern or post-imperial entities - deploy and prioritise different types of museums (based on art, archaeology, culture and ethnography) in their making, this book constitutes the first comprehensive and comparative perspective on national museums in Europe and their intricate relationship to the making of nations and states.